2018
DOI: 10.1186/s12885-018-4511-6
|View full text |Cite
|
Sign up to set email alerts
|

PROstate Multicentre External beam radioTHErapy Using a Stereotactic boost: the PROMETHEUS study protocol

Abstract: BackgroundHigh Dose Rate Brachytherapy (HDRB) boost is a well-established treatment for prostate cancer (PC). We describe the PROstate Multicentre External beam radioTHErapy Using Stereotactic boost (PROMETHEUS) study. Non-surgical stereotactic techniques are used to deliver similar doses to HDRB boost regimens with a dose escalation sub-study.MethodsEligible patients have intermediate or high risk PC. PROMETHEUS explores the safety, efficacy and feasibility of multiple Australian centres cooperating in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Similarly with the increasing inclusion of the seminal vesicles in the target volume in recent trials will also further increase the dosimetric impact of these prostate tilts due to the elongation of the volume in the superior-inferior direction. 26 It can be seen that for both CTV and PTV the sphericity and CI are highly regular with very low variability. This would indicate that the patient population have very similar shaped prostates and that consistent planning outcomes are being achieved respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly with the increasing inclusion of the seminal vesicles in the target volume in recent trials will also further increase the dosimetric impact of these prostate tilts due to the elongation of the volume in the superior-inferior direction. 26 It can be seen that for both CTV and PTV the sphericity and CI are highly regular with very low variability. This would indicate that the patient population have very similar shaped prostates and that consistent planning outcomes are being achieved respectively.…”
Section: Discussionmentioning
confidence: 91%
“…SBRT prostate clinical trial protocols specify the CTV to PTV margins to be used in treatment planning [19][20][21]. While there is no consensus for standardized margin values for prostate SBRT across all trials, clinical sites participating in a given trial should have positioning and immobilization techniques that meet the specified CTV-PTV margins in the study protocol.…”
Section: Discussionmentioning
confidence: 99%
“…A phase II study of prostate SBRT (35 Gy in five fractions) using volumetric modulated arc therapy and flattening free 10 MV photons, which specified CTV to PTV margins of 3-5 mm in each direction, found that the treatments were feasible and tolerated in an acute setting [19]. The PROMETHEUS study protocol, exploring the safety, efficacy, and feasibility of a two fraction SBRT boost, specifies a CTV to PTV margin of 5 mm everywhere except posterior where it is 3 mm [20]. The Novel Integration of New prostate radiation schedules with adJuvant Androgen deprivation (NINJA) clinical trial is a randomized study comparing two emerging SBRT regimens (a five fraction and a two fraction) for efficacy specifies a 3 mm uniform CTV to PTV expansion for SBRT treatments [21].…”
Section: Discussionmentioning
confidence: 99%
“…The set-up for the primary planning CT was to be the same as for treatment (e.g., with or without IDC). Full technical details have been described previously (11).…”
Section: Methodsmentioning
confidence: 99%
“…A dose of 46 Gy in 23 daily fractions was prescribed using IMRT or VMAT with daily image guidance. Dose constraints for the EBRT component have been outlined previously (11). Following publication of the PROFIT and CHHIP hypofractionation studies, the protocol was amended in 2017 to allow an alternate EBRT fractionation schedule of 36 Gy in 12 daily fractions (1315).…”
Section: Methodsmentioning
confidence: 99%